Fabrication of photoluminescent electrospun poly(styrene-co-methyl methacrylate) nanofibers integrated with LaPO4:Eu3+ for optical applications. (2021) - Varkey, Vinitha; Chandran, Aswathy R.; Tomlal Jose, E.; Paul, Issac; Jose, Gijo
Abstract: Organic luminescent nanofibers owing to their flexibility and anisotropic emission along the axis when compared to direction perpendicular to axis are gaining much importance as luminescent probes and in a variety of other optic applications. Of the different organic luminescent nanofibers the one which is of recent interest is the rare earth integrated electrospun polymeric nanofibers. Among different host matrices the most suitable one is polymer in view of electrospinning technique as it facilitates the spinnability of the solution which is a matter of concern when coming to electrospinning technique and also enhances the flexibility of the product. Rare earths are the most apt material of choice when the research focus into luminescent applications. Among a number of rare earths of choice the one with greater potential is undoubtedly europium ion because of its intense emission in the orange red region on UV excitation. In the present study the polymer chosen is poly (styrene-co-methyl methacrylate) which is a copolymer of polystyrene and polymethyl methacrylate and the rare earth integrated is LaPO4 :Eu 3+ . The surface morphologyanalysis and optical characterizations are done by SEM, EDX, XRD, PL and IR techniques. The sem analysis shows that the average fiber diameter distribution increased from the range of 70 nm to 120 nm on integration of LaPO4 :Eu 3+ . The shift of maximum excitation wavelength in the UV spectra and presence of characteristic bands of Eu 3+ ions in the region 579 to 610 nm in the integrated nanofibers shows that the rare earth is very well distributed into the polymer matrix. Also there is significant enhancement in the intensity of integrated nanofiber.